2022
DOI: 10.1177/00031348221142573
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Automated Reminder Calls in a Safety-Net Setting on Surgical Clinic No-Show Rates

Abstract: In surgical clinics, missed appointments may lead to delayed diagnosis and postponed surgical intervention. Automated reminder calls (robocalls) have replaced live staff phone calls in many systems as a cost-saving measure. This study aims to evaluate whether robocalls reduced the outpatient appointment no-show rate for surgical patients in a county hospital. Demographic and clinic data from two surgical clinics at a safety net hospital were collected over two time periods: 3-months immediately before robocall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…Moreover, a key feature of standardisation is that it ensures that anaesthetists and surgeons are aligned regarding pre-operative workup and cancellation decisions. Second, and perhaps more importantly, the study emphasises the importance of preoperative communication with patients in reducing sameday cancellations and corroborates similar reports in other hospital settings [5,6]. Text messages in particular represent a low-cost, accessible and potentially automatable way of ensuring that patients show up for scheduled surgery and may be especially impactful given that mobile telephone use is nearly ubiquitous globally, including in low-and middle-income countries [7].…”
supporting
confidence: 81%
“…Moreover, a key feature of standardisation is that it ensures that anaesthetists and surgeons are aligned regarding pre-operative workup and cancellation decisions. Second, and perhaps more importantly, the study emphasises the importance of preoperative communication with patients in reducing sameday cancellations and corroborates similar reports in other hospital settings [5,6]. Text messages in particular represent a low-cost, accessible and potentially automatable way of ensuring that patients show up for scheduled surgery and may be especially impactful given that mobile telephone use is nearly ubiquitous globally, including in low-and middle-income countries [7].…”
supporting
confidence: 81%
“…A before-after study within the general surgery clinic of a safety net hospital in Southern California demonstrated that automated "robocalls" independently reduced the no-show rate. 26 While these automated messages do appear to be effective, a large, randomized trial in 2016 revealed that live-person phone calls 1 week prior to scheduled internal medicine appointments increased attendance compared to automated messages. 27 Extensive work in this field stimulated a Cochrane review analyzing eight randomized controlled trials with 6,615 patients, finding limited evidence that text messaging reminders may improve clinic attendance compared to no reminders or postal reminders.…”
Section: Discussionmentioning
confidence: 99%
“…A before-after study within the general surgery clinic of a safety net hospital in Southern California demonstrated that automated "robocalls" independently reduced the no-show rate 26 .…”
Section: Appointment Reminders Are Also Routine Interventions Designe...mentioning
confidence: 99%